2020
DOI: 10.1080/13607863.2020.1843001
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, social network size, and mortality in older adults and the role of cortisol

Abstract: Background: Loneliness and social isolation have both been found to be associated with increased mortality in previous studies. One potential underlying mechanism is via the hypothalamic-pituitary-adrenal axis.Objective: This study aimed to examine the association between social network size and cortisol, to analyze the associations between both loneliness and social network size and mortality, and to examine to what extent the association between network size and/or loneliness and mortality is mediated by cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…We also failed to find a relationship between loneliness and DCS. This result agrees with other previous studies (Schutter et al, 2017(Schutter et al, , 2020Montoliu et al, 2019), although it contrasts with studies that found a flattened DCS in married participants (Johar et al, 2021) and in a selected sample with extremely high loneliness scores (Cole et al, 2007). In both of these studies, the sample was composed of people who could suffer from alcohol abuse, smoking, or diabetes, which can influence the DCS (Adam et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also failed to find a relationship between loneliness and DCS. This result agrees with other previous studies (Schutter et al, 2017(Schutter et al, , 2020Montoliu et al, 2019), although it contrasts with studies that found a flattened DCS in married participants (Johar et al, 2021) and in a selected sample with extremely high loneliness scores (Cole et al, 2007). In both of these studies, the sample was composed of people who could suffer from alcohol abuse, smoking, or diabetes, which can influence the DCS (Adam et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have investigated the relationship between loneliness, the cortisol awakening response (CAR), and the diurnal cortisol slope (DCS) in aging, but with inconsistent results. In middle-aged adults, loneliness was found to be associated with CAR (Steptoe et al, 2004;Adam et al, 2006;Okamura et al, 2011), but no differences were found in CAR or DCS based on loneliness in older males and females (Schutter et al, 2017(Schutter et al, , 2020. However, in older people, a flatter DCS was found in lonely people in comparison with non-lonely individuals (Cole et al, 2007).…”
Section: Introductionmentioning
confidence: 88%
“…We report that loneliness is associated with an increased risk of AD and dementia, while no significant association between loneliness and MCI risk or VaD was observed. Loneliness has previously been identified as a risk factor for premature mortality ( Holt-Lunstad et al, 2015 ; Schutter et al, 2021 ), adverse biological parameters (e.g., hypertension), health-risk behaviors (including smoking, physical inactivity, and excess alcohol consumption), physical and mental morbidity, and increased health service use ( Hawkley et al, 2009 ; Shankar et al, 2011 ; Dyal and Valente, 2015 ). However, the strength of this relationship between loneliness and dementia remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness is experienced across the lifespan and across cultures. Most adults present transient symptoms of loneliness throughout the course of their lives ( Victor et al, 2020 ; Schutter et al, 2021 ). Symptoms of loneliness and social isolation overlap; however, loneliness has been shown to be independently associated with health outcomes ( Holt-Lunstad et al, 2015 ; Leigh-Hunt et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the effects of loneliness and social network size cannot be compared directly. Only two studies investigated both loneliness and social network size (Ellwardt et al 2015 ; Schutter et al 2020 ). One of these studies concluded that social network size was associated with mortality, but loneliness was not (Ellwardt et al 2015 ); the other study concluded that neither was associated with mortality (Schutter et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%